PENANAMAN NILAI-NILAI MORAL OLEH ORANG TUA DALAM KELUARGA MENURUT REMAJA DI JORONG KUBANG KENAGARIAN MAGEK KECAMATAN KAMANG MAGEK KABUPATEN AGAM - Fajrin Alfarabi (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2014)
This research in the background by the availability of good in JorongKubang.This study aims to describe the cultivation of moral values ​​in children by teenagers in the family in JorongKubangKenagarianMagekKecamatanKamangMagekKabupatenAgam. This research is descriptive quantitative. The population in this study were all teenagers at Jorongkubang totaling 26 people, A survey of data collection with the use of data collection tools and quisioner. While the techniques of data analysis using the percentage formula.From the results of the study found that the cultivation of moral values ​​in children in aspects: (1) through habituation, (2) by example, (3) through advice, (4) through attention and (5) through rulemaking. From the above findings it can be concluded that the cultivation of moral values ​​in children by adolescents has been running well this is evident from the results of the percentage of each variable is declared good. General suggestion that the cultivation of moral values ​​can be enhanced and become a major concern by the parents in the family